Comportamentos sugestivos de transtornos alimentares na adolescência: aspectos conceituais: Risk behaviors for eating disorders in adolescents: conceptual issues - Souza Ferreira , julia Elba de; da Veiga, Gloria Valeria (Adolescência e Saúde, 2010)
Anorexia nervosa, bulimia nervosa and binge eating disorder are behavioral syndromes described as eating disorders, and not as diseases, because its pathogenesis is undefi ned. Although classifi ed separately, anorexia nervosa and bulimia nervosa are related by common psychopathology as: excessive worried with body weight. Individuals suffering from these disorders tend to have strict diets or use of compensation mechanisms for food intake (as purging through the use of laxatives, diuretics or self-induced vomiting). The binge eating episodes in bulimia nervosa, likewise, is a core feature of binge eating disorder, but in this case, there is no use of compensation mechanisms for food intake. The eating disorders are complex syndromes, whose origin is multifactorial, and several aspects related to its genesis, such as psychological, biological and socio-cultural. The current standards of beauty, focused on thinness is part of the genesis of eating disorders and contribute to its psychopathology. Adolescence is the age group most vulnerable to the eating disorders, because they are more infl uenced by the current standards of beauty focused on thinness. This is an aggravating since these eating disorders could negatively impact on self-esteem and body satisfaction and could trigger to malnutrition or obesity.